CORTICOSTEROIDS AND SECONDARY INFECTIONS: AN INSIGHT INTO CORONAVIRUS DISEASE-2019 - NEELA, BHARGAVI; JAKKULA, SHIRISHA; MUJEEBUDDIN; PRATAP GAUR, RAVINDRA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Coronavirus disease 2019 (COVID-19), which is caused by novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged at Wuhan in China in December 2019 and has rapidly spread throughout the world. The droplets expelled during face-to-face exposure, mainly through talking, coughing, or sneezing, are the most common mode of transmission. So far, children have not been affected frequently without deaths. However, the course of this virus in the future is unknown. The diagnosis is mainly made through reverse transcription-polymerase chain reaction (RT-PCR) and serology testing. Treatment with dexamethasone at an early phase of developed acute respiratory distress syndrome (ARDS) caused by SARS-CoV-2 alters the pulmonary and systemic inflammatory response and decreases mortality. Corticosteroid therapy is associated with a sizable reduction in the duration of mechanical ventilation and hospital mortality. One of the major risk factor associated with corticosteroid therapy is associated with acquiring secondary infections. Pulmonary epithelial damage and inflammatory disease are the predisposing risk factors for pulmonary aspergillosis due to the release of danger molecular patterns during severe COVID-19. Galactomannan and culture testing of bronchoalveolar lavage fluid are the most sensitive diagnostic measures for aspergillosis in intensive care unit (ICU). Finally, the treatment of coronavirus associated pulmonary aspergillosis is complex. The only way one can prevent the spread of infection by following precautions such as frequent hand washing, wearing a mask in public places, social distancing, and by avoiding unnecessary gatherings.